2020
DOI: 10.1002/ente.202000885
|View full text |Cite
|
Sign up to set email alerts
|

Solid‐State Reoxidation Kinetics of A/B‐Site Substituted LaMnO3 During Solar Thermochemical CO2 Conversion

Abstract: Perovskite oxides exhibit noteworthy performance as efficient oxygen carriers for two‐step thermochemical conversion of CO2 using concentrated solar energy. Herein, the effect of composition on the solid‐state reoxidation kinetics of La0.5Sr0.5MnO3 and LaCo0.5Mn0.5O3 oxygen carriers is investigated. Thermochemical CO2 splitting reactions are conducted at several selected temperatures and a series of kinetic models are explored. Results indicate that the most suitable model describing the reoxidation mechanism … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 44 publications
0
3
0
Order By: Relevance
“…Correlations between the lattice geometric parameters of perovskite oxides and thermochemical redox CO 2 -splitting performance were also highlighted [134,135]. oxidation kinetics of A/B-site substituted LaMnO3 during thermochemical CO2 conversion were studied, showing that the re-oxidation mechanism varied depending on the composition of the oxygen carrier [133]. Correlations between the lattice geometric parameters of perovskite oxides and thermochemical redox CO2-splitting performance were also highlighted [134,135].…”
Section: Perovskite-based Cyclesmentioning
confidence: 87%
See 1 more Smart Citation
“…Correlations between the lattice geometric parameters of perovskite oxides and thermochemical redox CO 2 -splitting performance were also highlighted [134,135]. oxidation kinetics of A/B-site substituted LaMnO3 during thermochemical CO2 conversion were studied, showing that the re-oxidation mechanism varied depending on the composition of the oxygen carrier [133]. Correlations between the lattice geometric parameters of perovskite oxides and thermochemical redox CO2-splitting performance were also highlighted [134,135].…”
Section: Perovskite-based Cyclesmentioning
confidence: 87%
“…Another study revealed a production of CO of 114 µmol g −1 with La 0.6 Sr 0.4 Mn 0.6 Al 0.4 O 3 [132]. The solid-state re-oxidation kinetics of A/B-site substituted LaMnO 3 during thermochemical CO 2 conversion were studied, showing that the re-oxidation mechanism varied depending on the composition of the oxygen carrier [133]. Correlations between the lattice geometric parameters of perovskite oxides and thermochemical redox CO 2 -splitting performance were also highlighted [134,135].…”
Section: Perovskite-based Cyclesmentioning
confidence: 99%
“…Kinetic studies were performed to identify the most suitable models of solid-gas reactions for the reduction and oxidation steps [186]. Correlations were also established between geometric parameters of the crystalline structure of perovskites and the redox performances obtained during cycling [187].…”
Section: Cycles Based On Perovskitesmentioning
confidence: 99%